Changes of Gene Expression Patterns of Muscle Pathophysiology-Related Transcription Factors During Denervated Muscle Atrophy - Yang, Xiaoming; Li, Ming; Ji, Yanan; Lin, Yinghao; Xu, Lai; Gu, Xiaosong; Sun, Hualin; Wang, Wei; Shen, Yuntian; Liu, Hua; Zhu, Jianwei (Frontiers in Physiology, 2022)
Peripheral nerve injury is common, and can lead to skeletal muscle atrophy and dysfunction. However, the underlying molecular mechanisms are not fully understood. The transcription factors have been proved to play a key role in denervated muscle atrophy. In order to systematically analyze transcription factors and obtain more comprehensive information of the molecular regulatory mechanisms in denervated muscle atrophy, a new transcriptome survey focused on transcription factors are warranted. In the current study, we used microarray to identify and analyze differentially expressed genes encoding transcription factors in denervated muscle atrophy in a rat model of sciatic nerve dissection. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses were used to explore the biological functions of differentially expressed transcription factors and their target genes related to skeletal muscle pathophysiology. We found that the differentially expressed transcription factors were mainly involved in the immune response. Based on correlation analysis and the expression trends of transcription factors, 18 differentially expressed transcription factors were identified. Stat3, Myod1, Runx1, Atf3, Junb, Runx2, Myf6, Stat5a, Tead4, Klf5, Myog, Mef2a, and Hes6 were upregulated. Ppargc1a, Nr4a1, Lhx2, Ppara, and Rxrg were downregulated. Functional network mapping revealed that these transcription factors are mainly involved in inflammation, development, aging, proteolysis, differentiation, regeneration, autophagy, oxidative stress, atrophy, and ubiquitination. These findings may help understand the regulatory mechanisms of denervated muscle atrophy and provide potential targets for future therapeutic interventions for muscle atrophy following peripheral nerve injury.